Dogs' Eavesdropping from People's Reactions in Third Party Interactions - Freidin, Esteban (2013)
Eavesdropping involves the acquisition of information from third-party interactions, and can serve as an indirect mean to attribute reputation to individuals. There is evidence on eavesdropping in dogs according to which they can develop a preference for people based on their cooperativeness towards others. In this study, we tested dogs´ eavesdropping abilities one step further: we made them choose between cooperative demonstrators (the donors) who subjects observed interacting with a person asking for food (the beggar); here, the only difference between donors was not in their behavior but in whether the beggar reacted positively or negatively (through verbal and gestural means) to them. In fact, dogs preferred to approach the donor towards which the beggar reacted positively. Besides, in two other groups, we showed that neither the beggar´s body gestures nor the verbal component of the interaction on their own were sufficient to affect the dogs´ preferences. We also ran two further groups to test for the possibility of dogs´ choices being driven by local enhancement, but we did not find evidence of systematic place preferences. We conclude that dogs´ abilities to track reputation are more sophisticated than previously thought and may rely on multiple cues. We relate these findings to dogs´ phylogenetic domestication process and their ontogenetic reliance on humans to access valuable resources.